ANALISIS YURIDIS TENTANG PRAPENUNTUTAN DIKAITKAN DENGAN HAK ASASI MANUSIA TERSANGKA - Nadya Lestari Tua Manullang; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Alternating behind the prosecution of the case file to the investigator so contrary to the interests of the suspect or the principles of justice are fast, fair, free, simple, and inexpensive. The purpose of this thesis, namely: First, To Can Know In Prapenuntutan Problems Associated With Human Rights of Suspects, Second, To Know Settings Can Prapenuntutan In Criminal Case, Third, Can Knowing Due To Legal Prapenuntutan Against Investigation and Public Prosecution. This research uses normative juridical research method, the research done by first examining the materials library of the law relating to pemasalahan or study of regulations is standard / recorded, whereas the data source used, primary data, secondary data, and data tertiary, data collection techniques in this research with the study of literature or study methods documentary. From the research there are three main issues that can be inferred. First, the problems in prapenuntutan associated with the human rights of suspects, that there are no settings to how many times prapenuntutan can be done. The absence of sanctions for investigators when the case file is not submitted to the public prosecutor. Secondly, setting prapenuntutan in criminal cases, while the settings are: the Code of Criminal Procedure which consists of Article 8, Article 14, Article 109, Article 110, Article 138, Article 139, Explanation of Article 30 of Law No. 16 of 2004 About Kejasaan, Attorney General of the Republic of Indonesia Regulation No. PER-036 / A / JA / 09/2011 on Standard Operating Procedures (SOP) General Crimes Case Management. Third, the result of Prapenuntutan Law Against Investigation and Public Prosecution, while the consequence that in the conduct of the police arrest should not be mistaken. The possibility of errors arrest may occur because the arrest was no reason authorized by law, Saran writer, first, should the Criminal Code should provide an explanation of the notion prapenuntutan the second Neither investigators nor prosecutors must be able to resolve the case files as possible in accordance the time limit prescribed by the law, third, So that there is no case files back and forth between the public prosecutor with the investigator, here the necessary firmness of the law enforcement agencies in order to carry out his duties can be as determined by law.Keywords: Prapenuntutan - Human Rights - Suspect